Biodegradation of oxidized high-density polyethylene and oxo-degradable plastic using microalgae Dunaliella salina. Issue 1 (31st December 2022) - Hadiyanto, Hadiyanto; Khoironi, Adian; Dianratri, Inggar; Huda, Khoirul; Suherman, Suherman; Muhammad, Fuad
ABSTRACT: This research aimed to evaluate the effectiveness of microalgae Dunaliella salina in the biodegradation process of oxidized oxium and HDPE plastics. Microalgae and microplastic interactions were evaluated in two 1 L glass bioreactors containing D. salina with oxium microplastics and oxidized HDPE at various concentrations (100 mg/500 mL, 200 mg/500 mL, and 300 mg/500 mL) for 15 d. The results showed a more significant decrease in alkene functional groups in oxium plastics than in HDPE. In addition, there was a change in the oxium functional group with the formation of carbonyl, ether, and primary alcohol. The growth rate of D. salina decreased significantly after interaction with oxidized HDPE microplastics compared to oxium interaction. We established that oxium plastics have a faster biodegradation ability owing to the addition of additives to the plastic. However, oxidation pre-treatment with H2 O2 on HDPE plastic can also accelerate the plastic degradation process.